Convergence liberalism and the problem of disagreement concerning public justification - Billingham, P (Taylor and Francis, 2017)
The ‘convergence conception’ of political liberalism has become increasingly popular in recent years. Steven Wall has shown that convergence liberals face a serious dilemma in responding to disagreement about whether laws are publicly justified. What I call the ‘conjunctive approach’ to such disagreement threatens anarchism, while the ‘non-conjunctive’ approach appears to render convergence liberalism internally inconsistent. This paper defends the non-conjunctive approach, which holds that the correct view of public justification should be followed even if some citizens do not consider enacted laws to be publicly justified. My argument sheds light on the fundamental structure of convergence liberalism.